Manajemen Kurikulum Pesantren dalam Membentuk Karakter Santri di Pesantren Darunnajah Al-Mas’udiyah Denpasar Tahun Pelajaran 2020/2021 - Uswatun Hasanah; Sudarsono; Nur Wahyudi (Nusantara Journal of Islamic Studies, 2021)
Pesantren is an Islamic educational institution that grows and is recognized by the surrounding community and has its own characteristics, kiai as leader figures and students as objects given religious knowledge and dormitories as a place to live for students. Education aims to foster citizens to have Muslim personalities in accordance with the teachings of Islam and to instill this religious sense in all aspects of their lives and make them useful for religion, society, nation and state. The purpose of this study was to determine the curriculum management planning of Darun-Najah Al-Mas'udiyah Denpasar Islamic boarding school in shaping the character of students. The results of this qualitative research show that in planning the pesantren curriculum, the head of the Darun Najah Al-Mas'udiyah Islamic Boarding School Denpasar carries out a work program. management, in the Darun Najah Al-Mas'udiyah Islamic Boarding School Denpasar, routine evaluations are carried out once a month or quarterly.